BAITUL MAAL WA TAMWIL DIGITALIZATION AND MILLENNIALS ACCEPTANCE IN INDONESIA - Salama, Sri Cahyaning Umi; Millatina, Afifah Nur; Ajija, Shochrul Rohmatul; Hudaifah, Ahmad; Johari, Fuadah (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2025)
Digitalization in microfinance institutions, including Sharia-compliant ones such as Baitul Maal wa Tamwil (BMT), is considered crucial for several reasons, including operational efficiency, increased financial inclusion, and rising demand in the evolving financial ecosystem. As a crucial tool for alleviating poverty and empowering marginalized communities, the integration of digital technology has become a necessity, not an option. This research examines the factors that influence millennials’ use of digital financial technology developed by BMT. This study employed the Technology Acceptance Model (TAM) processed through Structural Equation Modeling (SEM) in SmartPLS with 108 respondents. The sample consisted of millennial- generation Islamic digital BMT users in Indonesia who have at least one experience using it. The sampling technique used was accidental sampling, and data collection was carried out for one month. The results indicated that all hypotheses were accepted. Ease of use significantly affected users' attitudes, as did the usefulness for behavior. This finding implies that if a digital BMT platform is easier to use, it will lead to more positive attitudes among its users. , the more useful a digital BMT platform is, the more positively its users will behave and the more likely they will be to use it in the future.